Answer:
2) ![\frac{\sqrt{77}}{11}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B77%7D%7D%7B11%7D)
3) 5√2
Step-by-step explanation:
Simplest radical form of an expression is the expression in radical so that there are no more square roots, cube roots, 4th roots, etc left to find, after rationalising the denominator ( if needed ).
2. Here the given expressions,
![\frac{\sqrt{7}}{\sqrt{11}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B7%7D%7D%7B%5Csqrt%7B11%7D%7D)
For rationalising the denominator multiply both numerator and denominator by √11,
![\frac{\sqrt{77}}{11}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B77%7D%7D%7B11%7D)
3. given expression,
![\sqrt{50}](https://tex.z-dn.net/?f=%5Csqrt%7B50%7D)
![=\sqrt{25\times 2}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B25%5Ctimes%202%7D)
![(\because \sqrt{ab}=\sqrt{a}\sqrt{b})](https://tex.z-dn.net/?f=%28%5Cbecause%20%5Csqrt%7Bab%7D%3D%5Csqrt%7Ba%7D%5Csqrt%7Bb%7D%29)
![=5\sqrt{2}](https://tex.z-dn.net/?f=%3D5%5Csqrt%7B2%7D)
Linear because x moves up by 3 and y moves up by 7
Answer:
what........???????............
Answer:
1) Multiplying powers with the same base would be product rule. It where you just add the exponents. Dividing powers with the same base would be the quotient rule. Its where you subtract the exponents.
2)Where you multiply the two exponents together
3)The negative law is where for example, if it were in the numerator, then it would be placed at the denominator with a positive exponent whereas if it were in the denominator it would be on the numerator with the positive exponent. The zero law just states the anything to the power to zero is one.
Step-by-step explanation:
1) 3^3 x 3^4 = 3 ^3+4 = 3^7
3^9 ÷3² = 3^9-2 = 3^7
2) (3^2)^2 = 3^2×2 =3^4
3) 1/3^-5 = 3^5 \
3^-7 =1/3^7
2^0 = 1
Answer:
x = 5
or
x = 3
Step-by-step explanation:
The first term is, x2 its coefficient is 1 .
The middle term is, -8x its coefficient is -8 .
The last term, "the constant", is +15
Step-1 : Multiply the coefficient of the first term by the constant 1 • 15 = 15
Step-2 : Find two factors of 15 whose sum equals the coefficient of the middle term, which is -8 .
-15 + -1 = -16
-5 + -3 = -8